1999
DOI: 10.1046/j.1464-410x.1999.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

To determine whether the temperature of 2% lignocaine gel affects the initial discomfort which may be associated with its instillation into the male urethra

Abstract: Objective To determine whether the temperature of 2%Results Compared with the control group (at 22°C), there was a statistically significant reduction in pain lignocaine hydrochloride gel aCects the initial discomfort during instillation into the male urethra. score in the group receiving cold gel (Student's t-test, P<0.05). Patients and methods Sixty consenting men were randomized to receive 11 mL of 2% lignocaine hydroConclusion The cooling of 2% lignocaine gel significantly reduced the initial discomfort as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…So many studies had examined different methods to reduce male patients' discomfort, such as assessment of the volume of lidocaine, 10 increasing hydrostatic pressure by squeezing the irrigation solution bag, 11 cooled lignocaine gel, 12 simultaneous visualization, 13 application of nitrous oxide inhalation, 14 slow delivery of local anesthetics, 15 use of 740 ZHANG ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…So many studies had examined different methods to reduce male patients' discomfort, such as assessment of the volume of lidocaine, 10 increasing hydrostatic pressure by squeezing the irrigation solution bag, 11 cooled lignocaine gel, 12 simultaneous visualization, 13 application of nitrous oxide inhalation, 14 slow delivery of local anesthetics, 15 use of 740 ZHANG ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…We slowly delivered intraurethral lidocaine and plain lubricating gel in all patients. Thomson, Goel et al [22,23] reported that cooling the lidocaine gel to 4°C significantly reduced the discomfort compared to the same agent at 22°C. However, Bhomi et al [2] reported cooled lidocaine gel at 4°C has no advantage over room temperature lidocaine gel for decreasing pain perception during rigid cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…It is a lipid soluble amide base that is capable of entering the hydrophobic components of neuronal cell membranes and preventing the transmembrane flow of sodium ions necessary for the initiation and propagation of nerve signal action potentials [3,6]. It is usually marketed as its hydrochloride salt, with a pH of 4-6 to increase both the solubility and shelf-life [3,7].…”
Section: Discussionmentioning
confidence: 99%
“…To this effect, over 30 years ago, Boggia [4] demonstrated that warming local anaesthetic agents results in decreased discomfort. Thompson et al [3], on the other hand, have recently demonstrated the opposite. They have shown, in a prospective, double-blind, randomised study that cooling of 2% lignocaine gel to 4°C, compared with 22°C (room temperature) or 40°C, significantly reduces the initial discomfort associated with its delivery into the male urethra [4].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation